2015
DOI: 10.1261/rna.049262.114
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing uncovers novel long noncoding and small nucleolar RNAs dysregulated in head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma persists as one of the most common and deadly malignancies, with early detection and effective treatment still posing formidable challenges. To expand our currently sparse knowledge of the noncoding alterations involved in the disease and identify potential biomarkers and therapeutic targets, we globally profiled the dysregulation of small nucleolar and long noncoding RNAs in head and neck tumors. Using next-generation RNA-sequencing data from 40 pairs of tumor and matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 45 publications
0
76
0
Order By: Relevance
“…DE of HOTAIR has been assessed in six independent studies analysing 323 patients with results supporting its overexpression (Arunkumar, Deva Magendhra Rao et al., ; Fang et al., ; Lu et al., ; Wu & Xie, ; Wu et al., ; Zou et al., ). Conversely, the only study that examined HOTAIR expression in dysplastic lesions did not find significant DE (Gibb et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DE of HOTAIR has been assessed in six independent studies analysing 323 patients with results supporting its overexpression (Arunkumar, Deva Magendhra Rao et al., ; Fang et al., ; Lu et al., ; Wu & Xie, ; Wu et al., ; Zou et al., ). Conversely, the only study that examined HOTAIR expression in dysplastic lesions did not find significant DE (Gibb et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Non‐significant DE was found in a study examining 60 OSCCs compared to a limited number of controls (eight cases) (Arunkumar, Deva Magendhra Rao et al., ). Of interest, a study addressing the TCGA data set identified a significant underexpression in OSCC but not in TSCC (Zou et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies have identified multiple functional effects of lncRNAs involving in various cellular processes, such as tumor initiation, progression and metastasis, and the dysregulation of lncRNAs are a primary feature of some human cancers [1619]. At the same time, a great quantity identified results revealed that lncRNAs play an important role in pathogenesis of head and neck cancers [2022]. However, the TSCC associated lncRNAs and their influence on TSCC cellular progress need to be elucidated further.…”
Section: Introductionmentioning
confidence: 99%
“…For example, FAM3D-AS1 is involved in the migration and cell proliferation in head and neck squamous cell carcinoma31, but our inferred functions in basal LUSC are RNA splicing and peptidyl-amino acid modification (Table S1). The inconsistency might be due to the difference in cancer cell types since lncRNAs may play different roles in different cell lines, tissues and cancers.…”
Section: Resultsmentioning
confidence: 99%